Effects of Pre‐Electroplated Metal or/and Graphene on the Initial Coulombic Efficiency of Graphite Anode. Issue 19 (3rd September 2021) - Shen, Wenzhuo; Ding, Haoyuan; Zhang, Jiali; Zhong, Min; Guo, Shouwu
Abstract: Formation of solid electrolyte interface (SEI) and irreversible electrochemical reactions on the surface of anode during the lithiation/delithiation are considered as the main factors affecting the initial Coulombic efficiency of lithium‐ion battery. In this work, different metal or/and graphene is pre‐electroplated on the surface of graphite powder using a home‐built electrochemical workstation, and the surface states of graphite powder are characterized using FESEM, HRTEM, and TOF‐SIMS. The results show that metal or/and graphene are plated uniformly on the surface of graphite. The electrochemical property of the coin half‐cell using pre‐electroplated graphite as anodes shows that the metal can improve the electron/ion transfer capability of the composites that further suppress the irreversible reactions. The graphene can also control the formation of SEI on the anode, which counteract the considerable consumption of Li ions during the initial lithation/delithiation cycle. Abstract : A technique for pre‐electroplating metal or/and graphene on graphite powder is developed. Metal can improve the conductivity of graphite to further suppress side reactions and graphene can control the formation of the solid electrolyte interface layer on anode. As a result, the graphite/Sn/rGO, and graphite/Li composites show improved initial coulombic efficiency, larger specific capacity, higher rate capability and better cyclic stability as anode materials for LIBs.